Konversi Masyarakat Terasing: Studi Tentang Perubahan Sosial Masyarakat Suku Laut di Pulau Air Mas, Kota Batam - , ELSA FITRI ANIS; , Abdul Gaffar Karim, SIP, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Change is something that certainly happens in a society, whether its occur gradually or rapidly, and desired or not. Invariably for people who are classified as isolated communities as well as Suku Laut society located in Air Mas island, one of the islands in the area of Batam. They live in the midst of the environment and the communities in which the change occurs very quickly. This is because the Batam city located in the province of Kepulauan Riau is a very strategic area and has great potential in the development and regional development in the fields of trade, industry, and tourism. So that the development efforts undertaken by both government and the private sector have an impact on their communities and they are forced to adapt to these changes. And then what extents it affects to Suku Laut society and how Suku Laut society response to these changes. Therefore, this study was conducted to answer the big questions about how the process of social change that occurs in the Suku Laut society in Air Mas island. This research was conducted qualitatively by observation and depth interviews with actors or parties involved in the process of social change that occurred in the Suku Laut society. Parties such as the Suku Laut, Lembaga Amil Zakat of Masjid Raya Batam (LAZ MRB), local governments, and society activists or observers of the Suku Laut become an important actor to be observed and interviewed to obtain further explanations and thorough understanding and detail. Furthermore, groups of people outside the Suku Luat also needs to be observed so that we can know how the pattern of relations between them. Not only that, documents such as images, article and so on are also important in this study to support the data obtained from observations and interviews. Suku Laut society is a native tribe in the Riau Islands that have traditions and beliefs tend to be different from the surrounding society. They are considered uneducated because of their wandering lifestyle in the ocean and have no religion because they beliefs as animism. With such a variety of reasons, they are categorized as a tribal society that must be converted to align with the development efforts undertaken by the government, especially during the Order Baru government through Pelita (Pembangunan Lima Tahun). With a variety of considerations, they had laid off and forced to choose one religion that is approved by the state, and Islam was choosed as religion field in their identity card (KTP). One is because of since the Age of Malay kingdoms Suku Laut society already know Islam, so Islam is not a stranger, even some their traditions or cultures are also influenced by Islam. However, the attempt failed because the Suku Laut people themselves are not ready to adapt to these changes, so they prefer to return to their previous lives, which is wandering in the ocean. The attempt of conversion was followed by non-government actors such as activists or observers of Suku Laut as well as the Lembaga Amil Zakat of Masjid Raya Batam (LAZ MRB) with a different approach through coaching and mentoring in a variety of things, including religion. This method is considered successful, as evidenced by the increasing number of Suku Laut settled and take Islam nor other islam as their religion. Thus, major changes faced by the Suku Laut including the cultural, traditional, even religious belief is a long process that has been run slowly and can not be avoided. They live in the midst of an environment that continues in the development and modernization, so inevitably they also have to accept the conversion so that they can be recognized and live as equals with other citizens and be able to access various resources and their rights properly.